Banished potentates : dethroning and exiling Indigenous monarchs under British and French colonial rule, 1815-1955 - Aldrich, Robert, 1954- (Studies in imperialism (Manchester, England), 2018)
An examination of British and French deposition and exile of Indigenous monarchs in Asia and Africa from 1815 until the 1950s.